The Multiplier, Flexible Exchanges, and International Equilibrium - Stolper, W. F. (Quarterly Journal of Economics, 1950)
I. Introduction, 559. — II. International equilibrium with flexible exchanges, 560. — III. Purchasing power parity reformulated, 566. — IV. Dynamic interactions, 569; the final equilibrium, 572. — V. Conditions determining which income will be greater, 576. — VI. Conditions determining whether incomes will be greater with or without flexible exchanges, 577. — VII. Conclusions, 579. — Appendix, 580.